Transisi Menuju Blended Learning Pasca-Pandemi: Evaluasi Efektivitas dan Kesiapan Infrastruktur Pendidikan - Lovy Herayanti; Gunawan Gunawan; Fahmi Yahya (Indonesian Publication Center, 2021)
The COVID-19 pandemic triggered a massive disruption in global education, compelling a rapid shift from conventional instruction to emergency remote teaching. As the educational landscape stabilizes, the transition toward a structured blended learning model has emerged as a strategic priority. This narrative review evaluates the effectiveness of blended learning and assesses the readiness of educational infrastructure in the post-pandemic era. By synthesizing 18 selected academic publications, this study identifies three critical themes: the conceptual shift from emergency remote teaching, the effectiveness of various digital platforms, and the interplay between infrastructure readiness, teacher competence, and stakeholder involvement. The findings reveal that while diverse digital platforms have successfully maintained learning continuity, the efficacy of blended learning is deeply contingent upon digital literacy, sound pedagogical design, and systemic technical support. Furthermore, the study highlights that psychological well-being and active parental engagement are essential components for sustainable implementation. It is concluded that the successful integration of blended learning requires a holistic approach, prioritizing equitable infrastructure investment, continuous professional development for educators, and flexible policy frameworks. These measures are vital to ensure an inclusive and resilient educational ecosystem capable of navigating future challenges.